A colorimetric sensor for the sequential detection of Cu2+ and CN− in fully aqueous media: practical performance of Cu2+1. Issue 19 (21st May 2015) - You, Ga Rim; Park, Gyeong Jin; Lee, Jae Jun; Kim, Cheal
<x xml:space="preserve">Abstract</x> A colorimetric chemosensor was synthesized for sequential detection of Cu2+ and CN−, and used to detect and quantify Cu2+.